How to tackle challenging ChIP-Seq, with long-range cross-linking, using ATRX as an example - Truch, J; Telenius, J; Higgs, D; Gibbons, R (Springer, 2018)
Chromatin immunoprecipitation coupled with high-throughput, next-generation DNA sequencing (ChIP-seq) has enabled researchers to establish the genome-wide patterns of chromatin modifications and binding of chromatin-associated proteins. Well-established protocols produce robust ChIP-seq data for many proteins by sequencing the DNA obtained following immunoprecipitation of fragmented chromatin using a wide range of specific antibodies. In general, the quality of these data mainly depends on the specificity and avidity of the antibody used. However, even using optimal antibodies, ChIP-seq can become more challenging when the protein associates with chromatin via protein-protein interactions rather than directly binding DNA. An example of such a protein is the alpha-thalassaemia mental retardation X-linked (ATRX) protein; a chromatin remodeler that associates with the histone chaperone DAXX, in the deposition of the replication-independent histone variant H3.3 and plays an important role in maintaining chromatin integrity. Inherited mutations of ATRX cause syndromal mental retardation (ATR-X Syndrome) whereas acquired mutations are associated with myelodysplasia, acute myeloid leukemia (ATMDS syndrome), and a range of solid tumors. Therefore, high quality ChIP-seq data have been needed to analyze the genome-wide distribution of ATRX, to advance our understanding of its normal role and to comprehend how mutations contribute to human disease. Here, we describe an optimized ChIP-seq protocol for ATRX which can also be used to produce high quality data sets for other challenging proteins which are indirectly associated with DNA and complement the ChIP-seq toolkit for genome-wide analyses of histone chaperon complexes and associated chromatin remodelers. Although not a focus of this chapter, we will also provide some insight for the analysis of the large dataset generated by ChIP-seq. Even though this protocol has been fully optimized for ATRX, it should also provide guidance for efficient ChIP-seq analysis, using the appropriate antibodies, for other proteins interacting indirectly with DNA.